Churches of Public Works in the Dutch province of Guelderland (Bulletin KNOB, 1992)
For a long time the name ‘Churches of Public Works’ was automatically given to the neoclassical Churches from the second quarter of the 19th century, which went up under the supervision (and partly after the plans) of engineers of the department of Public Works. The construction of these churches was State-aided. This name concerned simple brick hall churches without columns with a white-plastered interior and a peristyle or pilaster facade on the front, crowned with an elegant cupola-tower. Research in the Dutch province of Guelderland however proved that examples of the churches as described above mostly were planned by individual architects. The department of Public Works was responsible for subsidized projects of poor, mostly catholic municipalities.The state only subsidized what was absolutely necessary. The engineers removed columns, pilasters and cupolas from the plans of individual architects in consideration of finances. Churches, built under the supervision of the Department of Public Works thereby mostly were unadorned brick buildings in which functionality prevailed.The three Standard types, which gradually developed in Guelderland stood out by format and not by artistic composition. The smallest variety was a one-aisled hall church without columns constructed back to back with the presbytery and with an unpretentious ridge turret on the facade. If money was available the second type often was provided with a simple tower. Only the largest variety had three aisles, mostly with the middle nave and side-aisles under one continuous hipped roof.Exuberance was not realizable to the Catholics in Guelderland. The assumption that the Department of Public Works only tolerated the classical style is not true, Gothic plans by individual architects were not excluded. The department however objected to the blending of style, for example the combination of gothic vaults and classic pilasters. The pure application of style was the first consideration.